Association between race/skin color and premature birth: a systematic review with meta-analysis - Oliveira, Kelly Albuquerque de; Araújo, Edna Maria de; Oliveira, Keyte Albuquerque de; Casotti, Cesar Augusto; Silva, Carlos Alberto Lima da; Santos, Djanilson Barbosa dos (Revista de Saúde Pública, 2018)
OBJECTIVE: To analyze the association between race/skin color and the occurrence of prematurity. METHODS: Meta-analysis with observational studies, selected by a systematic review in the bibliographic databases Medline and Biblioteca Virtual da Saúde with the descriptors: “Race or ethnic group” and “ethnicity and health” associated with the words “infant premature” and “obstetric labor premature”. Articles published in the period from 2010 to 2014, of the observational epidemiological type, in Portuguese, English and Spanish, were included. Articles that did not have abstracts or that were review articles, theses, dissertations, and editorials were excluded. We adopted the relative risk and their respective confidence intervals (95%CI) as measures of effect, obtained through the random effect model and represented by the forest plot type graph. The Egger test and the Newcastle-Ottawa scale, respectively, were used to analyze possible publication biases and the quality of the studies. RESULTS: Of the 926 articles identified, 17 were eligible for the study. Of the 17 full texts published, seven were retrospective cohort studies, nine were cross-sectional studies, and one was a case-control study. Except for one study, the others reported a positive association between race/color of skin and prematurity. Compared with full-term newborns, the relative risk of the combined effect in those born preterm was 1.51 (95%CI 1.39-1.69). The funnel chart suggested publication bias. CONCLUSIONS: The present meta-analysis indicated a positive association for the risk of prematurity according to race/skin color.